Stability Analysis of the Left Bank Slope of Baihetan Hydropower Station Based on the MF-DFA Method - Haoyu Mao; Min Zhang; Biao Li; Nuwen Xu (Advances in Civil Engineering, 2020)
Based on the left bank slope of Baihetan hydropower station in Southwestern China, a high-precision microseismic monitoring system was established. An early warning model of surrounding rock mass deformation and failure based on MF-DFA was proposed. The results showed that the multifractal characteristics of the microseismic and blasting waveform time series in the left bank slope were obvious, and the multifractal spectrum width of the blasting waveform is much larger than that of microseismic waveform. Before the slope cracks increased, the multifractal time-varying response characteristics of microseismic waveform showed strong regularity, which could be regarded as a precursor of surrounding rock mass deformation. Before the deformation and failure of surrounding rock mass, the multifractal spectrum width Δα showed an increasing trend while the multifractal spectrum of microseismic waveforms Δf(α) presented a decreasing trend, which can be regarded as a precursor of surrounding rock mass deformation; when deformation and failure occurred, Δα showed a decreasing trend and Δf(α) showed an increasing trend, which can be regarded as a deformation failure period; after the occurrence of deformation and failure, both Δα and Δf(α) showed a steady trend, and Δf(α) would approach to the zero line, which can be regarded as a stable period.